Geotourism Assessment using the M-GAM method (Modified Geosite Assessment Model) Sawahlunto Region, West Sumatra - Dezilia, Dieny; Harnani, Harnani (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2023)
The geological setting in the area is a strong attraction for natural tourism. The Sawahlunto Geopark area is one of the Geoparks located in West Sumatra Province which has a variety of geological sites. This area meets the criteria that make it a potential Geopark. The purpose of this analysis is to evaluate the potential of geotourism and use this assessment as a basis for developing geotourism in the Sawahlunto and surrounding geotourism areas. This analytical study was carried out using the M-GAM (Modified Geosite Assessment Model) method. In the study process, research methods were carried out using questionnaire data based on 27 indicators from the M-GAM method.M-GAM method has 27 indicators consisting of main and additional values that will be used as a questionnaire which will produce quantitative results. The 27 indicators contain several geotourism assessments, including scientific value, aesthetic value, protection value, functional value, and tourism value of a geosite. The maximum score that can be obtained by a geosite that has all the perfect criteria in 27 indicators will get a main score of 12 and an additional score of 15. 7 geosites will be assessed with results, namely Batu Runciang (8.17 and 7.62), Serpih Bakelok (6.35 and 7.72), Tabiang Tinggi (6.81 and 8.14) and Puncak Cemara (8.19 and 8.41), Stone Garden (6.37 and 7.96), Batu Gantuang Cave (3.91 and 6.07) and Kubang Waterfall (3.48 and 6.48). Referring to the results of the Sawahlunto geosite assessment, it was concluded that the Batu Runciang and Puncak Cemara Geosites had a high value in terms of main values compared to the other 5 geosites. Meanwhile, for additional value, Tabiang Tinggi and Puncak Cemara have sufficient value compared to the other 5 Geosites. This is because geosites with low value still lack various things such as facilities and promotions. Efforts that can be made are to build facilities at several geosites that still experience a lack of public facilities. Apart from that, promotion on social media is also very helpful in introducing geosites to the public.